An approach for children's emergent literacy adaptive activities - Mombach, Jaline Gonçalves; de Souza, Paulo Silas Severo; Soares, Fabrizzio A. M. N.; Rossi, Fábio Diniz; Ferreto, Tiago Coelho; Leal, Lara (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2019: Anais do XXX Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/cbie.sbie.2019.489, 2019)
In the educational field, there is a concern about helping children to develop emergent literacy skills such as reading and writing. However, this is not a trivial task since children may have different needs based on their skill levels. In this sense, we present an approach that employs mobile and cloud computing technology to adapt activities from different subjects according to children skill levels. Besides, our proposal generates assessment reports so teachers can monitor children achievement in real time. Experiments were conducted, and the results were positive, showing that our proposal could ease the development of adaptive activities and improve children engagement.